The investigational meningococcal serogroups A, C, W-135 and Y tetanus toxoid conjugate vaccine (ACWY-TT) and the seasonal influenza virus vaccine are immunogenic and well-tolerated when co-administered in adults - Mari Rose Aplasca-De Los Reyes; Efren Dimaano; Noel Macalalad; Ghassan Dbaibo; Véronique Bianco; Yaela Baine; Jacqueline M. Miller (Human Vaccines & Immunotherapeutics)
Co-administration of meningococcal serogroups A, C, W-135 and Y conjugate vaccine (ACWY-TT) with seasonal influenza vaccine was investigated in a subset of adults enrolled in a larger study evaluating lot-to-lot consistency of ACWY-TT and non-inferiority to licensed tetravalent meningococcal polysaccharide vaccine (MenPS). Subjects in this sub-study were randomized (3:1:1) to receive ACWY-TT alone (ACWY-TT group) or with seasonal influenza vaccine (Coad), or licensed MenPS alone. Serum bactericidal antibodies (rSBA) and serum haemagglutination-inhibition (HI) antibody titers were measured pre- and 1 mo post-vaccination. Non-inferiority of the Coad group compared with ACWY-TT group was demonstrated in terms of rSBA geometric mean antibody titers (GMTs) to serogroups A, W-135 and Y. For serogroup C the pre-defined non-inferiority limit was marginally exceeded. Post-vaccination rSBA GMTs were significantly higher (exploratory analysis) in the Coad group compared with the MenPS group for serogroups A, W-135, and Y and were similar to the MenPS group for serogroup C. Overall, > 97% of subjects achieved rSBA titers ≥ 1:128 for all serogroups. The Coad group met all criteria defined by the Committee on Human Medicinal Products (CHMP) for seroprotection, seroconversion and seroconversion factor for HI antibodies for all three influenza strains. Grade 3 solicited local/general symptoms were reported by ≤ 1.9% of subjects in any group. These data support the co-administration of ACWY-TT with seasonal influenza vaccine when protection is needed against both diseases.   This study is registered at clinicaltrials.gov NCT00453986